Extensive Intracardiac and Deep Venous Thromboses in a Young Woman with Heparin-Induced Thrombocytopenia and May-Thurner Syndrome - Yekaterina Kim; Daniel C. Choi; Ali N. Zaidi (Case Reports in Hematology)
A 38-year-old woman with a history of recurrent deep venous thromboses (DVTs) on chronic anticoagulation presented with acute left leg swelling. The patient was diagnosed with an acute left lower extremity (LLE) DVT in the setting of May-Thurner syndrome for which treatment with unfractionated heparin was started. Her hospital course was complicated by a new diagnosis of heparin-induced thrombocytopenia (HIT), with an incidental discovery of a large tricuspid valve mobile mass on a transthoracic echocardiogram (TTE). Subsequent imaging confirmed multiple right atrial thrombi along with LLE venous stent thrombosis and a new right LE acute DVT. Anticoagulation with argatroban for HIT thrombosis was started. She underwent a right atrial percutaneous thrombectomy and bilateral lower extremity thrombectomy with directed angioplasty and stent placement. This presentation is a rare manifestation of HIT with extensive intracardiac and deep venous thrombi, with successful staged interventions.